EPPOCRATIS: Expedited Preoperative Point-of-Care Reduction of Fractures to Normalized Anatomy and Three-Dimensional Printing to Improve Surgical Outcomes. Issue 3 (March 2022) - Sharaf, Basel; Kuruoglu, Doga; Cantwell, Sean R.; Alexander, Amy E.; Dickens, Hunter J.; Morris, Jonathan M.
Abstract : Summary: Virtual surgical planning and three-dimensional printing have been invaluable tools in craniomaxillofacial surgery. From planning head and neck reconstruction to orthognathic surgery and secondary reconstruction of maxillofacial trauma, virtual surgical planning and three-dimensional printing allow the surgeon to rehearse the surgical plan and use patient-specific surgical guides for carrying out the plan accurately. However, the process of virtual surgical planning and three-dimensional printing requires time and coordination between the surgeon on one hand and the biomedical engineers and designers on the other hand. Outsourcing to third-party companies contributes to inefficiencies in this process. Advances in surgical planning software and three-dimensional printing technology have enabled the integration of virtual surgical planning and three-dimensional printing at the treating hospital, the point of care. This allows for expedited use of this process in semiurgent surgical cases and acute facial trauma cases by bringing the surgeon, radiologist, biomedical engineers, and designers to the point of care. In this article, the authors present the utility of EPPOCRATIS, expedited preoperative point of care reduction of fractures to normalized anatomy and three-dimensional printing to improve surgical outcomes, in the management of acute facial trauma.